Data analytic framework for crime sector using open grid rule generation algorithm - Sharmila begum, M; George, A (International Journal of Engineering and Technology, 2018)
Data analyticsÂ (DA) is the process of exploringÂ datasets in order to illustrate conclusions about the information they contain. It is a process of inspecting, cleansing, transforming, and modelingÂ dataÂ with the goal of discovering useful information. A database contains both structured and semi-structured data. The semi-structured data are from different sources. The system is provided with an open grid rule generationfor analyzing the data from whole data container. According to this concept, the analysis is much absolute rather than other, data mining technique.The main objective of the proposed study is to provide data having better and significant perspective.Â